Implications of a Changing China for Brazil : A New Window of Opportunity? - World Bank (Washington, DC, 2014)
As Brazil and China have become two of the largest global economies, they have also become increasingly connected. Three decades of fast-paced growth and structural change have turned China into the world s second-largest economy and have transformed it into an upper-middle income country. Brazil, which had experienced its own episode of high growth between 1965 and 1974, has also become one of the largest economies. Over the last decade, Brazil and China have developed increasingly close linkages, which has come as no surprise given the scale of their economies, the complementary structure of resource endowments as well as the differences between the two countries in the structure of production and demand. This report examines how structural change in China is expected to present new opportunities and challenges for Brazil to enhance its global position and energize growth. Building on recent work (World Bank and Development Research Center, 2013), this report identifies three potential longer-term transformations of the Chinese economy structurally slower growth, a rebalancing on the demand and supply side, and a move up the value chain and examines their implications for Brazil. The report shows how the slowdown and rebalancing of China may also present new opportunities for Brazil, even if China s progression up the value chain is likely to present also new challenges. It lays out how Brazil could generate greater benefits from its interactions with China and how the changes in China would offer a new window of opportunity for Brazil to press ahead with its structural reform agenda. Overall, Brazil could gain tremendously from the anticipated structural changes in China, even though realizing these gains will require a proactive policy stance to enhance external ties and address internal growth and productivity constraints.